As implicações do Novo Ensino Médio para o ensino de Química e a metodologia CTSA - Carius, Luane Barbara Rissi (2024)
THE IMPLICATIONS OF THE NEW HIGH SCHOOL FOR CHEMISTRY TEACHING AND THE CTSA METHODOLOGY. The New High School was mandatorily implemented in all education systems in 2022 and is included in the Law of Guidelines and Bases of Brazilian Education - LDB, which contains all the changes resulting from the High School Reform, aiming mainly at Youth Protagonism through the integral formation of the student - physical, cognitive and socio-emotional formation. Thus, given the relevance of this educational reform, this research aimed to analyze what were the implications in Chemistry Teaching after the adoption of the New High School in the different education systems - Public Full-Time School, Public Professional Technical School and Private School through the study of the changes contained in law 13.415/2017 and its similarities with the CTSA methodology and Freirean pedagogy. For this purpose, documentary research with content analysis, the researcher's field diary, semi-structured interviews with teachers and the application of a closed questionnaire with students in the second year of high school were used as data collection instruments. In the documentary research with content analysis, it was possible to include the assessment of official documents - LDB and BNCC (National Common Curricular Base) and the main changes resulting from law 13.415/2017. The field diary presents the researcher's reflections on the New High School, analyzing how this new model was implemented in the different education systems. In the semi-structured interview applied to the teachers, it was possible to analyze an overview of acceptance or not of the implementation of the New High School and its challenges. Finally, it was possible to discuss the students' perceptions about acceptance or rejection of the New High School through the results of the closed questionnaire, which analyzed the Youth Protagonism, Motivation, Teaching-Learning Process and Future Aims of these students, components present in the purposes of the New High School. Although the implementation of the New High School presents significant differences in the different education systems, this research showed that teachers and students presented similar and unfavorable perceptions of the new model, allowing a reflection on possible points that need changes to improve the quality of education.